Humanitarian Aid from the Islamic Mass Organizations in Indonesia to Palestine - Andriansyah, Yuli (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2024)
The editorial in this issue highlights how humanitarian aid to Palestine has become a symbol of solidarity among Indonesians. It examines two major Islamic mass organizations in Indonesia, Nahdhatul Ulama and Muhammadiyah, and how they mobilize their resources and members to support Palestinian relief. The two organizations show a strong commitment to supporting the Palestinian cause before the current war on Gaza, which started in October 2023. This commitment to helping the Palestinian struggle is also in line with the position of the Indonesian government and academics.